ANALISIS TINGKAT PELAYANAN DAN TINGKAT KEPENTINGAN PELANGGAN PT. TELEKOMUNIKASI INDONESIA Tbk. SANGATTA - Heriyanto Heriyanto (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2015)
Objective Knowing the level of service and the level of customer interest PT.Telekomunikasi Tbk Branch Sangatta and knowing the dominant influence of factors of reliability, responsivenes, assurance, empathy, and tangible to customer satisfaction PT.Telekomunikasi Indonesia Tbk Sangatta branch.The results of the analysis proceed with the discussion that the average rate level of concordance between the service implementation PT. Telkom Tbk Branch Sengata with customer expectations of that X ̿ = 2.89 and Y = 3.83.Most attribute spread in Quadrant C are: provision of service time in accordance with the promise made, speed and accuracy in administrative services, keluangan time employees to respond to customers with precise, sense of security while dealing with staff / employees, employee patience, attention to the customer company, understanding of customer needs and the condition of the human resources company this suggests that some factor less importance for the Customer, its implementation by the management of PT. Telkom Tbk Branch Sengata just plain ordinary. Considered to be less important and less satisfying.PT. Telkom Tbk Branch Sengata have a commitment to excellence in running the service implementation conformance with the plan, the accuracy of the data, the ability of Human Resources, support the leadership of the company to task staff / employees, recency perlaatan and technologies, infrastructures and alignment conditions means the physical facilities with the type of services rendered ,PT. Telkom Tbk Branch Sengata have a weakness in terms of clarity of the submission of information and support services led the company to task staff / employee where the implementation is still not in accordance with customer expectations.